تنفيذ وسائط التعليم الفيديو المتحركة الأبعاد الثانية في مادة المطالعة في الفصل الثاني E بمهد والي صاعا عابر فونوروكو - Suryadarma, Yoke; Aldini, Arifandhy (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah, 2024)
However after getting observation, many teachers have not utilized learning media to help them deliver the information so that many students felt bored and this was a factor which make student scores not too high. The purpose of this study is to describe the implimention of 2D animated video learning media in muthala'ah learning in class 2E of Wali Songo Islamic Boarding School Ngabar Ponorogo in the academic year 2023-2024. This research used descriptive qualitative research methods. The data collection techniques used were: 1) Observation, 2) Interview and 3) Documentation with three analysis data namely: display data, data reduction and drawing conclusion. The results show that the steps of implementing 2D animated video learning media in muthala'ah come with three steps, 1) Opening 2) Essence Activity 3) Closing. Based on that, this research is really expected to be a reference for teachers to apply and develop innovative learning media to support the Arabic  learning process. أسس معهد والي صاعا وهو معهد قائم على نظام الوقف عام 1961. حيث يطبق هذا معهد منهج تعليم اللغة العربية في نظامه التعليمي. بعد الملاحظة، لم يستخدم العديد من المعلمين وسائط التعلم لمساعدتهم على تقديم المواد حتى يشعر الطلاب بالملل. وهذا عامل في انخفاض نتائج تعلم الطلاب. ويهدف هذا البحث إلى وصف تطبيق وسائط التعلم بالفيديو المتحركة الأبعاد الثانية في مادة المطالعة في الفصل الثاني E بمعهد والي صاعا عابر فونوروكو للعام الدراسي 2023-2024. هذا البحث منهج البحث النوعي الوصفي. كانت أساليب جمع البيانات المستخدمة هيالملاحظة، والمقابلة والتوثيق.  وأما تيحليل البحث فهي ثلاث مراحل: عرض البيانات، التخفيض وأخذ الاستبياط. ونتيجة هذا البحث أنهي كشف عن خطوات تنفيذ وسائط التعليم بالفيديو المتحركة الأبعاد الثانية في مادة المطالعة التي لها فعالة لدي الطلاب. ومن خلال هذا البحث، يرجى هذا البحث أن يكون مرجعا للمعلمين لتطبيق وتطوير وسائط تعليمية مبتكرة لدعم عملية تعليم العربية.